Reflexes of Proto-Ryukyuan *i and *u in Miyakoan as a chain shift - Jarosz, Aleksandra (Lingua Posnaniensis, 2018)
Thus, the conditions for identifying Miyakoan reflexes or *i and *u are listed and specified in this paper. Conversely, it is argued that unless one of these conditions has been met, one should reconstruct a Proto-Ryukyuan mid-vowel rather than a close vowel. Such specification may influence the comparative study of Ryukyuan languages to a significant degree, challenging a number of the so far established reconstructions (most notably Thorpe 1983).